The Protection of Human Rights under the ECHR and Central Europe: the Czech Republic - Grygar, Tomáš (European Integration Studies, 2025)
This paper examines the protection of human rights under the ECHR in the Czech Republic, emphasizing the historical evolution of human rights protection in the territory of the present-day Czech Republic, constitutional aspects of the application of the ECHR, the nation’s relationship with the Council of Europe (CoE) and landmark cases involving the Czech Republic before the ECtHR. Czechoslovakia was the first post-communist country that ratified the ECHR. However, the process of readmission of the independent Czech Republic to the Council of Europe after the dissolution of Czechoslovakia and the subsequent retroactive binding of the ECHR on the Czech Republic has been associated with several problematic issues from the perspective of public international law doctrine. This article points out that this retroactive application of the ECHR effectively violated Art. 59 (1) of the ECHR [former Art. 66 (1)], which provides that the ECHR shall be open to the signature of the members of the Council of Europe only. The paper also discusses in more detail a position of the ECHR in the Czech legal order and, above all, the constitutional background to its application. It draws attention to the problematic jurisprudence of the Czech Constitutional Court, according to which human rights treaties, including the ECHR, are not only part of the Czech legal order, but even of the “constitutional order”. This conclusion is contrary to Article 10 and Article 112(1) of the Czech Constitution. Landmark cases involving the Czech Republic before ECtHR reveal its evolving legal landscape. Notable cases include D.H. and Others v. Czech Republic, concerning alleged discrimination against Roma children in education. It is one of the first cases ever decided (not unanimously) by the Grand Chamber.